Toxicity of Prudhoe Bay Crude Oil to Alaskan Arctic Zooplankton - O'Brien, W. John (ARCTIC, 1978)
Bioassay experiments were conducted to determine the relative susceptibilities of three arctic zooplankton species to oil pollution, and the results were compared with the effects of an actual oil spill on a pond near Barrow. In both the bioassays and the pond, the addition of Prudhoe Bay crude oil was toxic to fairy shrimp (Branchionecta paladosa O. F. Müller), which seemed most sensitive, Daphnia middendorffiana Fischer, which was next most susceptible and Heterocope septentrionalis Juday and Muttkowski, which appeared somewhat resistant to the effects of oil. Cyclopoid copepods were the only common zooplankters able to survive the pond oil spill, and these were still present two and one half weeks after the spill. The rapid deaths of the other species, especially the branchiopods, suggest that zooplankton may be the most susceptible of all arctic freshwater organisms to oil pollution.